2009
DOI: 10.1111/j.1742-1241.2009.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial remodelling in hypertrophic cardiomyopathy: relation with exercise capacity and biochemical markers of tissue strain and remodelling

Abstract: Enlarged LAV is associated with impaired functional NYHA class and inversely with treadmill exercise capacity. Enlarged LAV is also associated with NT-pro-BNP, MMP-2 and CRP, perhaps as markers of disease severity and tissue remodelling. Age, LAV and NT-pro-BNP are independent predictors of exercise performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…[12], [29] Each millimeter enlargement of the left atrium elevated the risk of adverse outcomes by 4–9%. Interestingly, although left atrial diameter is highly associated with AF, [30] we observed that its effect was independent from AF for the progression to heart failure and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[12], [29] Each millimeter enlargement of the left atrium elevated the risk of adverse outcomes by 4–9%. Interestingly, although left atrial diameter is highly associated with AF, [30] we observed that its effect was independent from AF for the progression to heart failure and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged LAV has been shown to be associated with inflammation and atherosclerosis. 26,27 As cuff-tube placement around the femoral artery caused increases in the gene expression levels of inflammatory cytokines and chemokines, such as interleukin-1b and -6 and monocyte chemoattractant protein-1 in HCII-deficient mice compared with the levels in wild-type mice, 14 there is a possibility that HCII prevents LA enlargement partly through its anti-inflammatory potency leading to attenuation of left atrial remodeling. As LAV is an indicator of the burden of diastolic dysfunction, even in patients without atrial fibrillation or significant valvular heart disease, 28 our results indicated that plasma HCII activity could be involved in the pathogenesis of left ventricular diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although NT-proBNP levels (7,26) and LA functions (18) were shown to be associated with functional capacity in these patients, the relation between NT-proBNP levels and LA phasic functions has not been extensively documented.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma NT-proBNP levels were correlated with impaired functional capacity, predicting mortality and morbidity in patients with HCM (5,6). Several determinants of high plasma NT-proBNP levels have been demonstrated (7), but the relationship with LA phasic functions has not been extensively evaluated in patients with HCM. Therefore, in this study we investigated the LA phasic functions in patients with HCM, and assessed the relationship with symptomatic state and plasma NT-proBNP levels.…”
Section: Introductionmentioning
confidence: 99%